THE INFLUENCE OF SOCIAL MEDIA USAGE ON BODY IMAGE PERCEPTION AND HEALTH AMONG UNIVERSITY STUDENTS: ROLE OF PEER INFLUENCE AS THE MODERATOR - Galvin Tan Yit Chieng; Mohamad Azhari Abu Bakar, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Idealised body image shared by peers on social media platforms has been associated with negative body image perception and a higher risk of disordered eating attitudes among university students. However, there is still a lack of research studies on peer influence on social media usage on body image and health (disordered eating attitudes). This research aimed to investigate the influence of social media usage on body image perception and health (disordered eating attitudes), with the presence of peer influence as the moderating factor. Correlational research was conducted (N=153) using simple random sampling. The results indicated that social media usage has a significant influence on body image perception and health (disordered eating attitudes). However, peer influence does not moderate the relationships suggesting that social media usage still plays a huge role on body image perception and health (disordered eating attitudes) without the presence of peer influence.